2017
DOI: 10.1090/conm/683/13720
|View full text |Cite
|
Sign up to set email alerts
|

Categorical actions on unipotent representations of finite classical groups

Abstract: We review the categorical representation of a Kac-Moody algebra on unipotent representations of finite unitary groups in non-defining characteristic given in [18], using Harish-Chandra induction and restriction. Then, we extend this construction to finite reductive groups of types B or C in non-defining characteristic. We show that the decategorified representation is isomorphic to a direct sum of level 2 Fock spaces. We deduce that the Harish-Chandra branching graph coincides with the crystal graph of these F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Remark 7.8. In the context of modular representations of finite classical groups, there is a characterisation of cuspidal unipotent modules by Dudas, Varagnolo and Vasserot [6,Theorem 5.11] similar to Shan and Vasserot's characterisation of finitedimensional modules for cyclotomic Cherednik algebras. Therefore, we obtain an explicit description of these cuspidal modules which is exactly that of Theorem 7.7 with l = 2, see also [6,Section 5.5.3].…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 7.8. In the context of modular representations of finite classical groups, there is a characterisation of cuspidal unipotent modules by Dudas, Varagnolo and Vasserot [6,Theorem 5.11] similar to Shan and Vasserot's characterisation of finitedimensional modules for cyclotomic Cherednik algebras. Therefore, we obtain an explicit description of these cuspidal modules which is exactly that of Theorem 7.7 with l = 2, see also [6,Section 5.5.3].…”
Section: 3mentioning
confidence: 99%
“…In a recent preprint [25], Losev has given a combinatorial interpretation of this categorical action, but without using Uglov's approach to the Fock space. Finally, in the context of finite classical groups, it has been shown that H plays a role in the study of unipotent modular representations, by relating the notion of weak cuspidality to the classical one, see [6,Section 5].…”
Section: Introductionmentioning
confidence: 99%
“…This is completely analogous to Harish-Chandra series in Lie theory. In the case of finite unitary groups in positive, non-defining characteristic, the parametrization of Harish-Chandra series by cuspidal pairs is known to coincide with the parametrization of the Harish-Chandra series of a sum of type B Cherednik algebras, see [7].…”
Section: Integral Parametersmentioning
confidence: 99%
“…(1) First, we use Harish-Chandra induction and restriction to produce projective indecomposable modules (PIMs); (2) Second, we compute the missing PIMs (corresponding to cuspidal simple modules) using some partial information on the decomposition of Deligne-Lusztig characters on PIMs. For both of these steps, we use a truncated version of the Harish-Chandra induction and restriction coming from the categorical sl 2n -action on unipotent representations defined in [13]. The recent unitriangularity result in [4] allows us to compute the branching graph for this truncated induction, which provides the missing information for step (2) to be successful.…”
Section: Introductionmentioning
confidence: 99%